The Democratic Ideal vs. Luhmann’s Autopoietic Systems in Adult Education - Jeffrey Zacharakis (Adult Education Research Conference, 2017)
This paper analyzes the democratic ideal and its historical importance to adult education, and then analyzes how adult education today fits Niklas Luhmann’s autopoietic systems at the expense of the democratic ideal.
Keywords: Adult Education; Democratic Ideal; System’s Theory